Bilateral Asymmetric Dislocations of Hip Joints: An Unusual Mechanism of Injury - Rajesh Kumar Kanojia; Satya Ranjan Patra; Sumit Gupta (Case Reports in Orthopedics)
Asymmetric bilateral dislocations of the hips are rare injuries. Among the small number of reports in the literature, most have attributed the cause to high-velocity motor crashes. These dislocations are often seen to be associated with fractures of the proximal femur or the acetabulum. We present a case of a 45-year-old man with bilateral asymmetric dislocation of hips which were purely ligamentous in nature, without any fracture. He sustained his injuries due to a fall while getting on a moving bus. It was an unusual mechanism of injury as compared to the other cases of asymmetric hip dislocations reported in published studies. Both hips were reduced under general anaesthesia within three hours of the trauma. Skin traction and non-weight-bearing rehabilitation were continued for six weeks. After 35 months of followup, the patient remains asymptomatic. Early diagnosis and timely reduction of such dislocations under anaesthesia are necessary for prevention of complications.